An intermeshing electron transporting layer for efficient and stable CsPbI2Br perovskite solar cells with open circuit voltage over 1.3 V. Issue 29 (14th July 2020) - Liu, Shuo; Chen, Weijie; Shen, Yunxiu; Wang, Shuhui; Zhang, Moyao; Li, Yaowen; Li, Yongfang
Abstract : An intermeshing SnO2 ETL is designed and introduced into CsPbI2 Br-based inorganic pero-SCs, leading to improved PCE accompanied by reduced E loss . Abstract : Inorganic CsPbI2 Br perovskite has gained great attention due to its outstanding overall stability and great potential for application in semitransparent and tandem solar cells. However, the power conversion efficiencies (PCEs) of CsPbI2 Br-based perovskite solar cells (pero-SCs) are being limited by their severe energy loss ( E loss ) due to the unfavorable device interface and defects. Here, an intermeshing SnO2 (Im-SnO2 ) electron transporting layer (ELF) is subtly constructed by combining two types of SnO2 with complementary electronic/physical properties for suppressing the notorious E loss . With this strategy, the defects of the conventional SnO2 ETL can be greatly improved, which could simultaneously facilitate charge extraction, increase the crystallinity and orientation of CsPbI2 Br films, and form a cascade energy level in the device. Consequently, the E loss of CsPbI2 Br pero-SCs can be remarkably reduced to below 0.6 eV, delivering an excellent PCE of 16.10% with a V oc as high as 1.31 V. To the best of our knowledge, these results are among the best reported for a few CsPbI2 Br pero-SCs that enable high V oc without sacrificing efficiency. In addition, the devices show high stability under both strong UV irradiation for 300 h and an ambient atmosphere for 1000 h.